2017
DOI: 10.1002/cssc.201601883
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous AuIII Extraction and In Situ Formation of Polymeric Membrane‐Supported Au Nanoparticles: A Sustainable Process with Application in Catalysis

Abstract: A polymeric membrane-supported catalyst with immobilized gold nanoparticles (AuNPs) was prepared through the extraction and in situ reduction of Au salts in a one-step strategy. Polymeric inclusion membranes (PIMs) and polymeric nanoporous membranes (PNMs) were tested as different membrane-support systems. Transport experiments indicated that PIMs composed of cellulose triacetate, 2-nitrophenyloctyl ether, and an aliphatic tertiary amine (Adogen 364 or Alamine 336) were the most efficient supports for Au extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 87 publications
0
3
0
Order By: Relevance
“…Other research groups mentioned the use of membranes presenting embedded NPs. Mora-Tamez et al [ 66 ] reported on the implementation of Au NPs immobilized cellulose triacetate-based membranes. To this purpose, membranes composed of cellulose triacetate were prepared in the presence of some plasticizers (i.e., 2-nitrophenyl octyl ether and Adogen ® 364) and semi-interpenetrated with an inorganic phase prepared by sol-gel process in the presence of poly(dimethylsiloxane) and tetraethoxysilane.…”
Section: Structured Hybrid Materials For Catalyzing Molecular Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other research groups mentioned the use of membranes presenting embedded NPs. Mora-Tamez et al [ 66 ] reported on the implementation of Au NPs immobilized cellulose triacetate-based membranes. To this purpose, membranes composed of cellulose triacetate were prepared in the presence of some plasticizers (i.e., 2-nitrophenyl octyl ether and Adogen ® 364) and semi-interpenetrated with an inorganic phase prepared by sol-gel process in the presence of poly(dimethylsiloxane) and tetraethoxysilane.…”
Section: Structured Hybrid Materials For Catalyzing Molecular Reactionsmentioning
confidence: 99%
“…Reproduced with permission from Elsevier Ltd.; ( C ) in situ generated Pt NPs supported on a GCMA-based monolith [ 60 ], Copyright 2016. Reproduced with permission from the Royal Society of Chemistry; and ( D ) Au NPs supported on a porous cellulose membrane [ 66 ], Copyright 2017. Reproduced with permission from Wiley-VCH Publishers.…”
Section: Figurementioning
confidence: 99%
“…However, since their natural abundance is limited, they are extremely expensive, increasing the need to develop more efficient and innovative catalysts. 1 Using a very thin layer of a noble metal over a non-noble metal nucleus not only reduces the amount of noble metal used, but has also been proved to modify the catalytic properties, which in many cases are enhanced as a result of the synergistic effects in the crystalline and electronic structures of the materials. [2][3][4] In the case of Fe/Pt nanoparticles (NPs), when iron is used as the crystal nucleus, the obtained catalysts display multiple advantages such as lower cost and easy recoverability due to the magnetic properties of Fe.…”
Section: Introductionmentioning
confidence: 99%